Prevalence and Predictors of Self-Medication with Antifungal Drugs and Herbal Products Among University Students: A Cross-Sectional Study from Egypt - Khairy WA; Nasser HA; Sarhan MD; El Shamy A; Galal YS (Dove Medical Press, 2021)
Walaa Ahmed Khairy,1 Hebatallah A Nasser,2 Mai D Sarhan,3 Aliaa Ali El Shamy,2 Yasmine Samir Galal1 1Public Health and Community Medicine Department, Faculty of Medicine, Cairo University, Cairo, Egypt; 2Microbiology Department, Faculty of Pharmacy, Heliopolis University, Cairo, Egypt; 3Family Medicine Department, Faculty of Medicine, Cairo University, Cairo, EgyptCorrespondence: Walaa Ahmed KhairyPublic Health and Community Medicine Department, Faculty of Medicine, Cairo University, Kasr Alainy Street, Cairo, 11562, EgyptTel +20-1223682081Email Walaa.khairy@kasralainy.edu.egBackground and Purpose: Irrational use of drugs for self-medication (SM) is a worldwide public health problem which results in treatment failure, economic loss, and increased burden of morbidity and mortality. Thus, the purpose of this study was to explore SM with antifungal drugs and herbal products among university students in Egypt.Methods: A cross-sectional sectional study was conducted over 7 months among 403 university students in Egypt. The students were invited to complete a self-administered questionnaire through an online Google form. Questionnaire items included socio-demographic characteristics of the students, practice of and attitude towards SM with antifungal drugs, and SM with herbal products.Results: Prevalence of SM with antifungal drugs among students stood at 38.2%. The main reasons for SM with antifungal drugs were perceiving their health problem as being minimal, followed by having fears of a doctor’s visit. About 73% of the students thought that SM was not a safe practice. Older age (AOR = 1.5, 95% CI= 1.3– 1.8), affiliation to a private university (AOR = 3.7, 95% CI= 2.2– 6.4), and being a medical student (AOR =2.4, 95% CI= 1.3– 4.5) were the significant predictors of SM with antifungal drugs. A high prevalence of SM with herbal products (70.7%) was reported, with most students having used some form of herbal weight loss preparation (64%). Being a Cairo resident (AOR= 2.4, 95% CI =1.5– 3.8, P< 0.05) and being a medical student (AOR= 2.1, 95% CI =1.3– 3.4, P< 0.05) were the significant predictors of SM with herbal products.Conclusion: In the current study, SM was common among Egyptian university students. Providing counseling and public health education to university students with regards to SM is crucial. Implementing strict regulations and the full enforcement of excitant laws pertaining to the use of medication supplies is also needed. Herbal products should face the scrutiny of evidence-based medicine. Further studies are needed to evaluate the impact of SM among university students.Keywords: self-medication, antifungal, herbal, university, Egypt